2014
DOI: 10.1186/1753-6561-8-s1-s55
|View full text |Cite
|
Sign up to set email alerts
|

Population structure at different minor allele frequency levels

Abstract: Inferring population genetic structure from large-scale genotyping of single-nucleotide polymorphisms or variants is an important technique for studying the history and distribution of extant human populations, but it is also a very important tool for adjusting tests of association. However, the structures inferred depend on the minor allele frequency of the variants; this is very important when considering the phenotypic association of rare variants.Using the Genetic Analysis Workshop 18 data set for 142 unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 9 publications
1
23
1
1
Order By: Relevance
“…After SNPs were successfully identified, one SNP genotype per locus was exported from Stacks using the populations tool, retaining only SNPs with a minimum genotyping rate of 75% (−r 0.75) and a minimum minor allele frequency (MAF) of 3.3% (−min_maf 0.033), the lowest detectable MAF in at least one population of each species, following Massatti and Knowles (). Minimum MAF is an important parameter to consider because it can impact inference of genetic structure (De la Cruz & Raska, ). We therefore explored preliminary principal component (PC) analyses (see below) with minimum MAF = 1% and 5%, but found that using the higher minimum MAF (5%) made little qualitative difference in preliminary results.…”
Section: Methodsmentioning
confidence: 99%
“…After SNPs were successfully identified, one SNP genotype per locus was exported from Stacks using the populations tool, retaining only SNPs with a minimum genotyping rate of 75% (−r 0.75) and a minimum minor allele frequency (MAF) of 3.3% (−min_maf 0.033), the lowest detectable MAF in at least one population of each species, following Massatti and Knowles (). Minimum MAF is an important parameter to consider because it can impact inference of genetic structure (De la Cruz & Raska, ). We therefore explored preliminary principal component (PC) analyses (see below) with minimum MAF = 1% and 5%, but found that using the higher minimum MAF (5%) made little qualitative difference in preliminary results.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it has been shown that nonsynonymous SNPs are more likely to have a MAF less than 0.05 (Cargill et al, 1999) and alleles associated with environment can be significantly rarer than the average allele (Fournier-Level et al, 2011). In addition, studies including minor alleles with very However, SNPs with a low MAF may contribute to inconstant population structure estimates (De la Cruz & Raska, 2014;Mathieson & McVean, 2012). This can be overcome by removing minor alleles below the 0.05 threshold when estimating population structure.…”
Section: Variation In Sequencing Approaches and Genome Samplingmentioning
confidence: 99%
“…present in less than one per thousand people). These rare variants tend to be geographically restricted 29,30 or even private to an individual or family (Box 2). Rare variants also tend to be younger than common variants 31 .…”
Section: Rare Variants Deleterious Variantsmentioning
confidence: 99%